Immune priming modulates Galleria mellonella and Pseudomonas entomophila interaction. Antimicrobial properties of Kazal peptide Pr13a - Sułek, Michał; Kordaczuk, Jakub; Mak, Paweł; Śmiałek-Bartyzel, Justyna; Hułas-Stasiak, Monika; Wojda, Iwona (Frontiers in Immunology, 2024)
Galleria mellonella larvae repeatedly infected with Pseudomonas entomophila bacteria re-induced their immune response. Its parameters, i.e. the defence activities of cellfree hemolymph, the presence and activity of antimicrobial peptides, and the expression of immune-relevant genes were modulated after the re-challenge in comparison to non-primed infected larvae, resulting in better protection. No enhanced resistance was observed when the larvae were initially infected with other microorganisms, and larvae pre-infected with P.entomophila were not more resistant to further infection with other pathogens. Then, the peptide profiles of hemolymph from primed-and non-primed larvae infected with P. entomophila were compared by quantitative RP-HPLC (Reverse Phase -High Performance Liquid Chromatography). The level of carbonic anhydrase, anionic peptide-1, proline peptide-2, and finally, unknown so far, putative Kazal-peptide Pr13a was higher in the primed infected animals than in the larvae infected with P. entomophila for the first time.The expression of the Pr13a gene increased two-fold after the infection, but only in the primed animals. To check whether the enhanced level of Pr13a could have physiological significance, the peptide was purified to homogeneity and checked for its defence properties. In fact, it had antibacterial activity: at the concentration of 15 µM and 7.5 µM it reduced the number of P. entomophila and Bacillus thuringiensis CFU, respectively, to about 40 %. The antibacterial activity of Pr13a was correlated with changes observed on the surface of the peptide-treated bacteria, e.g. surface roughness and adhesion force. The presented results bring us closer to finding hemolymph constituents responsible for the effect of priming on the immune response in re-infected insects.